Comparative economics of offshore and mariculture facilities - Lisac D.; Muir J. (Mediterranean offshore mariculture, 2000)
A key concern for offshore aquaculture is the comparative investment cost of productive facilities and the consequent operating costs of production. This affects the decisions of potential producers to develop in offshore areas, the competitive potential of different production sectors in various regions, and the future opportunity for offshore system designers and manufacturers to develop and improve the sector. Based on contemporary data in the Mediterranean region, an outline is presented of the current capital and operating costs of typical systems, and of their comparative position with respect to land-based intensive aquaculture.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)